PENGARUH KOMPENSASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI DI KLINIK UTAMA DARKUTHNI KABUPATEN TOJO UNA - UNA PROVINSI SULAWESI TENGAH - Adriansyah, Adriansyah; Irfan, Andi; Pasulu, Milka; Dammar, Tria Haryuni (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the effect of compensation and work discipline on employee performance, with motivation as an intervening variable, at the Darkuthni Main Clinic in Tojo Una-Una Regency, Central Sulawesi. This study used a quantitative approach with a survey method among all employees. Data were collected through questionnaires and analyzed using Partial Least Squares-based structural equation modeling. The results indicate that compensation has a positive effect on performance, while work discipline has a positive effect on motivation. Motivation has been shown to improve employee performance and act as a mediator in the relationship between work discipline and performance. These findings confirm that improving discipline can boost motivation, which ultimately impacts performance, while appropriate compensation can directly improve performance. The practical implications of this study are the need for management to prioritize discipline programs, strengthen motivation, and refine a fair and competitive compensation system.